P108 The biology of a bronchiectasis exacerbation: changes in daily peak expiratory flow rate and symptoms before, during and afterwards. (14th November 2013) - Brill, SE; Bruce-Hickman, D; Leith, DJ; Singh, R; Mackay, AJ; Patel, ARC; Hurst, JR
Abstract : Introduction: Exacerbations of bronchiectasis are a major cause of morbidity in this neglected chronic lung disease. Little is known about the biology of these, and detailed daily changes in lung function and symptoms during their prodrome, onset and recovery have not been previously described. We prospectively investigated how lung function and symptoms change before, during and after a treated exacerbation of bronchiectasis. Methods: Bronchiectasis was confirmed on previous imaging and aetiology was determined according to BTS Guidance. Patients recorded their best morning peak expiratory flow rate (PEFR) and completed a daily diary card recording up to 15 symptoms and any treatment changes. Patients were also asked to attend the clinic and undertake spirometry if symptoms worsened. PEFR (% of best) and forced expiratory volume in one second (FEV1) at exacerbation (% predicted) were compared to baseline values at least two weeks from exacerbation symptoms. Results: Between August 2010 and July 2012 there were 42 exacerbations in 18 patients; the first in each patient was included for analysis. 15 patients were female; mean age was 60.7 years (SD 11.2) and baseline FEV1% predicted 79(33) (FEV1/FVC ratio 0.70(18)). Aetiology was post-infectious in 9 patients, idiopathic in 5, and other causes in 4. Between day -14 and day 0 (treatment initiation) there was a 9% drop in mean (SD) PEFR (92(6)% of best to 83(10)%, p < 0.001) and an increase in the mean daily symptom count from 1.2 (1.7) to 3.9 (2.1, p = 0.005). Figure 1 illustrates PEFR and daily symptoms across an exacerbation. Symptoms increase approximately 7 days prior to treatment start and PEFR drops 5 days prior. Following treatment initiation, symptoms improve faster than PEFR although recovery of both to pre-exacerbation values may take 30 days. There was no significant difference in the magnitude of the PEFR drop in patients with comorbid asthma (n = 5). There was a non-significant FEV1 drop of 1.7% predicted at exacerbation (n = 15). Conclusions: There is a significant drop in peak flow during exacerbations of bronchiectasis. This reflects changes in patients' symptoms and may persist for 30 days. Treatment was delayed for 7 days following the first rise in symptoms.